Integrating Blockchain Technology for Secure E-Government Services: Opportunities and Challenges - Hakimi, Musawer; Rahmani, Khoshal Rahman; Ezam, Zakirullah; Shahbazi, Hafizullah (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Blockchain technology offers tremendous promise for achieving higher levels of security, transparency, and efficiency in e?government service delivery. Governments around the world are actively pursuing the possibilities at stake, and understanding the opportunities and challenges becomes imperative for adoption. Purpose. This research will focus on how blockchain technology is incorporated into e-government services to increase security, economic benefits through integration with AI, improved activities on database performance by machine learning, ethical perspectives, and implications on future research. Method. A literature review was carried out mainly on databases including IEEE Xplore, ACM Digital Library, Scopus, Science Direct, Springer, and Google Scholar for papers dating from 2018 to 2024. Results. Key findings and insights were, therefore, extracted to give a full view of the envisaged blockchain role in government. Blockchain technology provides integrity, transparency, and decentralized governance to improve the security of e-government. Realization of economic impacts shall be seen through operational efficiency and cost savings, again through artificial intelligence in this integration. Conclusion. Machine learning algorithms bring optimality to database performance, enhancing scalability and responsiveness in large-scale applications of e-government. Essentially, ethics consider aspects of privacy, security, and public trust, which naturally would call for very strong regulatory frameworks and privacy-preserving mechanisms. Such integration of blockchain into e-government hence opens up a window of opportunity to change the operation, service delivery, and citizen engagement in the public sector. Such a study invites the implementation of R&D in recreating new adaptable regulatory frameworks, capacity building, and proactive public awareness campaigns. It also points out future research needs in the area of scalability solutions, interoperability, construction of privacy-preserving mechanisms, impact assessment, and successful governance models.